Susceptibility profile of Zimbabwean livestock fecal Escherichia coli isolates to veterinary antibiotics: Implications for standardization of antimicrobial resistance surveillance in livestock production - Anderson Munengwa; Chikumba Nation; Mugoti Alban; Dziwanyika Lenin (Syiah Kuala University, 2022)
Susceptibility patterns of Escherichia coli to Veterinary Critically Important Antimicrobials (VCIAs) are poorly understood in most developing countries. We determined those patterns on n = 180 livestock fecal isolates from Chikomba district by disk diffusion method. Multiple Antibiotic Resistance (MAR) indices for the isolates were determined for risk analysis. Chi-square was used to test how antibiotic susceptibility level associated with animal species and farming scale. Resistance to Tetracycline and Ampicillin was high across animal species (above 70%). Moderate levels of resistance (30% to 54%) to Erythromycin, Trimethoprim and Chloramphenicol were detected across livestock species. Resistance levels were low (below 30 %) for Ciprofloxacin and Gentamicin. Resistance to Gentamicin, Tetracycline, Ciprofloxacin, Ampicillin, Chloramphenicol and Ceftazidime was associated with animal species (P ˂ 0.05). Antibiotic susceptibility patterns were independent of farming scale (P 0.05). Frequencies of isolates within each risk zone depended on animal species (P ˂ 0.05), contrary to farming systems (P 0.05). Multi-Drug Resistance was 73%, where most isolates were resistant to 5 antibiotics (23%) and none exhibited resistance to all antibiotics. Only 55% of isolates from cattle and over 80% from pigs and layers were within the high risk zone. Twenty nine of the isolates were extended spectrum beta lactamase (ESBL) positive. Higher ESBL frequencies (44%) were observed within Large Scale Commercial Farms (LSCF) followed by for Small Scale Commercial Farms (SSCF) (25%) and Resettlement farms (A1) (14%). Similarly, ESBL prevalence varied by livestock species (P 0.05), as follows: pig (39%), layers (32%) and beef (12%). Our study suggests high incidences of multi-drug resistance in livestock which need AMR surveillance strategies. Keywords: Antibiotic resistance, Pigs, Poultry, Beef cattle, Escherichia coli